Spontaneous ovarian hyperstimulation syndrome following a thawed embryo transfer cycle - Kim, Mi Kyoung; Won, Hyung Jae; Shim, Sung Han; Cha, Dong Hyun; Yoon, Tae Ki (Clinical and experimental reproductive medicine, 2014)
This article reports a case of spontaneous ovarian hyperstimulation syndrome (OHSS) following a thawed embryo transfer cycle. OHSS, a potentially life-threatening condition, is an iatrogenic complication of controlled ovarian stimulation; therefore, it is very important to prevent and treat OHSS during treatment with ovulation-inducing agents. Despite our efforts to prevent OHSS, in this case, severe spontaneous OHSS occurred, which resulted in uncontrolled preterm labor and a preterm delivery and also persisted for 6 weeks after delivery. Freezing all embryos cannot entirely prevent the development of OHSS because OHSS can occur spontaneously. Although spontaneous OHSS remains a rare event, females with a history of OHSS may have an elevated risk for spontaneous OHSS. We suggest closely monitoring cases of pregnancy following thawed embryo transfer for early diagnosis of spontaneous OHSS and the use of conservative management.